Ecological Aspects of Social Evolution : Birds and Mammals. - Rubenstein, Daniel I. (Princeton legacy library., 2014)
Seeking common principles of social evolution in different taxonomic groups, the contributors to this volume discuss eighteen groups of birds and mammals for which long-term field studies have been carried out. They examine how social organization is shaped by the interaction between proximate ecological pressures and culture""--The social traditions already in place and shaped by local and phylogenetic history. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from t